Case report: A pregnant woman accidental treated with spironolactone in mid-gestation - Deng, Nianying; Zhong, Jiayi; Deng, Zhengjun; Chen, Minling; Yan, Liangqi; Li, Haiting; Han, Jiawei; Tao, Enfu (Frontiers in Pharmacology, 2024)
Spironolactone, a potassium-sparing diuretic, is used to treat hypertension, heart failure, and certain hyperandrogenic disorders. Its use during pregnancy is not recommended due to the risk of feminizing male fetuses, primarily because of its antiandrogenic activity. However, human data remain scarce and largely inconclusive.Here, we present the first case of a 25-year-old pregnant woman, at 16 weeks of gestation, who was inadvertently exposed to spironolactone (240 mg/day) for one week due to a pharmacy dispensing error. The patient subsequently delivered a healthy male infant with normal genitalia at 38 weeks of gestation following vaginal delivery. Current follow-up shows that the infant is healthy and developing normally.This article summarizes the potential causes of spironolactone-induced anomalous genital development and explores the safety of new-generation mineralocorticoid receptor antagonists (MRAs) during pregnancy. The mechanisms behind spironolactone-induced anomalous genital development in male fetuses have not been fully elucidated. Spironolactone competes with dihydrotestosterone for binding to androgen receptors and inhibits enzymes involved in androgen biosynthesis, which may partly explain its antiandrogenic effects. Recent advancements in MRAs have led to the development of compounds with higher selectivity for the mineralocorticoid receptor, thereby reducing the incidence of antiandrogen side effects. These new-generation MRAs may be effective alternatives during pregnancy, but more data are needed to establish their safety in pregnant women. This case contributes to the limited but growing body of literature on the safety profile of spironolactone in pregnancy, providing insights into its effects during a critical period of fetal development.